Ngempon: The Role-Sharing Strategy of Hindus and Muslims in Bhur Bwah Swah Temple, Karangasem, Bali - I Nyoman Yoga Segara (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
This article is the result of research on how Hindus and Muslims in Tabuan hill, Karangasem could live side by side in harmony. They showed it by becoming pengempon at Bhur Bwah Swah temple. Unlike in general, Muslims also take part in concurrently as pengempon. They actively maintain and carry out the ceremony every six months. The strong will of Muslims to be involved cannot be separated from their historical awareness of the past when they were welcomed and placed in Islamic villages by the king of Karangasem Kingdom. Furthermore, rites are a tool for them to re-dialogue past history to fulfill their needs. It is further used as guides of both religious people to maintain social solidarity. Symbolically, Muslims feel to be an inseparable part of the lives of Hindus since there is a santren in Bhur Bwah Swah temple. It is a sort of place where they perform prayers and celebrate saparan day every year. This research was conducted with a qualitative approach through an interview, observation, and document study techniques and utilize practice theory, precisely concerning the habitus developed by Pierre Bourdieu.